Acute anterior uveitis and Klebsiella aerogenes: a casual relationship?. Issue 11 (November 1981) - Willshaw, H E
Abstract : This study was undertaken to investigate the hypothesis that episodes of anterior uveitis in patients with the HLA B27 antigen are triggered by the presence of Klebsiella aerogenes in the gastrointestinal tract. Forty patients were examined. While the recovery of klebsiella was greater in B27 positive patients with uveitis, the differences failed to reach statistical significance. The clinical state of patients with Klebsiella aerogenes in their faeces did not differ from that in whom klebsiella could not be recovered.